Maintaining function and participation through tailored 24-hour movement behaviours for people living with multiple long-term conditions and frailty (The PERSONAL-AGILITY study): Protocol for a randomised controlled feasibility trial - Martha Thomas; Louisa Y. Herring; Melanie J. Davies; Lucina Wilde; Vicky Hall; Laura J. Gray; Sharlene A. Greenwood; Michelle Hadjiconstantinou; Malak Hamza; Andrew Harris; Jemma Hawkins; Kamlesh Khunti; et al. (PLoS ONE, 2026)
Introduction Maintaining function and participation through tailored 24-hour movement behaviours for people living with multiple long-term conditions (MLTC) and frailty (The PERSONAL-AGILITY study) is a research programme which aims to develop and evaluate a complex behaviour change intervention. The intervention uses a range of approaches tailored for individuals living with MLTC and frailty, and their carers, incorporating novel technology to improve 24-hour movement behaviours and, consequently, quality of life and physical function. This paper outlines the protocol for a randomised controlled trial (RCT) evaluating the feasibility and acceptability of the PERSONAL-AGILITY intervention, study design and procedures. Methods and analysis A feasibility RCT, with 2:1 allocation to the PERSONAL-AGILITY intervention or usual care control. The primary outcome is the feasibility and acceptability of a future definitive RCT investigating the effectiveness of the PERSONAL-AGILITY intervention, assessed against prespecified progression criteria, including eligibility, recruitment, retention, and outcome measure completion rates. The trial will be conducted at the University Hospitals of Leicester and comprise a 24-week tailored behaviour change intervention delivered by members of the PERSONAL-AGILITY research team. A target sample of 50 people with MLTC and frailty, and their carer (optional), will be recruited. A range of secondary outcomes including body composition, blood pressure, physical activity, sleep, physical function, and quality of life will be assessed at baseline, 12, and 24 weeks to help identify the primary or co-primary outcomes for participants with MLTC and frailty and their carers. A mixed methods process evaluation will examine the acceptability, feasibility and fidelity of intervention delivery and trial procedures. This study will inform the feasibility and design of a future definitive RCT. Ethics and dissemination The trial has been approved by South Central Oxford B Research Ethics Committee (Ref: 24/SC/0367). Participants will be asked to provide consent to take part in the PERSONAL-AGILITY study by a trained member of the research team. Findings will be disseminated via peer reviewed journals, presentations and communications with health care professionals, patients and the public. Trial registration: International Standard Randomised Controlled Trial Number 14362764. URL to registry record: https://www.isrctn.com/ISRCTN14362764 . Date of registration: 25 th November 2024.